FRANCISCO CKUKIWANCA Y LA OTRA JUSTICIA - ESPEZUA SALMON, BORIS GILMAR (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2020)
This article exalts the contribution that Francisco Chukiwamca Ayulo had in the Legal Indigenism that took place in the years 1910 and 1920 in southern Peru. Said contribution led to the rethinking of the socio-legal condition of the indigenous in order to achieve legal recognition and due protection in our national legislation. Francisco Chukiwanca not only demonstrated with his behavior and his social realization the closed defense in favor of the indigenous, but his anti-clericalism, as well as his left-wing political position, made him a respected lawyer in favor of the claims for indigenous rights, becoming a the most illustrious representative of Legal Indigenism of that time, along with personalities such as José A. Encinas. Ezequiel Urviola, Julián Palacios, Manual A. Quiroga who developed the vanguard of legal indigenism in the 20th century.